Subcellular localization and mechanism of secretion of vascular endothelial growth factor in human skeletal muscle. Issue 9 (24th May 2013) - Hoier, Birgitte; Prats, Clara; Qvortrup, Klaus; Pilegaard, Henriette; Bangsbo, Jens; Hellsten, Ylva
Abstract : The subcellular distribution and secretion of vascular endothelial growth factor (VEGF) was examined in skeletal muscle of healthy humans. Skeletal muscle biopsies were obtained from m.v. lateralis before and after a 2 h bout of cycling exercise. VEGF localization was conducted on preparations of teased muscle fibers by transmission electron microscopy (TEM) and confocal microscopy (CM). Muscle interstitial fluid was sampled from microdialysis probes placed in the thigh muscle. TEM and CM analysis revealed two primary sites of localization of VEGF: in vesicles located in the subsarcolemmal regions and between the contractile elements within the muscle fibers; and in pericytes situated on the skeletal muscle capillaries. Quantitation of the subsarcolemmal density of VEGF vesicles, calculated on top of myonuclei, in the muscle fibers revealed a 50% increase ( P <0.05) after exercise. The observation of more VEGF vesicles close to sarcolemma after exercise, combined with a 5‐fold increase ( P <0.05) in VEGF in the interstitial fluid, suggest that VEGF‐containing vesicles redistribute to sarcolemma and that VEGF is secreted to the extracellular fluid. This study provides the first evidence in humans for a mechanism by which skeletal muscle fibers can control capillary growth by releasing VEGF from intracellular vesicles during contraction.—Hoier, B., Prats, C., Qvortrup, K., Pilegaard, H., Bangsbo, J., Hellsten, Y., Subcellular localization and mechanism of secretion of vascular endothelial growth factor in human skeletal muscle. FASEB J. 27, 3496–3504 (2013). www.fasebj.org